2015
DOI: 10.1051/parasite/2015014
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofToxoplasma gondiiDNA in horse meat from supermarkets in France and performance evaluation of two serological tests

Abstract: In France, some cases of severe toxoplasmosis have been linked to the consumption of horse meat that had been imported from the American continent where atypical strains of Toxoplasma gondii are more common than in Europe. Many seroprevalence studies are presented in the literature but risk assessment of T. gondii infection after horse meat consumption is not possible in the absence of validated serological tests and the unknown correlation between detection of antibodies against T. gondii and presence of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
(37 reference statements)
1
29
0
Order By: Relevance
“…in [29, 30]). Recent studies in Europe have shown seropositivity rates of 1.7% in Greece [31], 10.8% in Spain [32], 3% [33] and 17.6% in Italy [34], 23% in the Czech Republic [35], 37.8% in Romania [36], and from 13 to 90% (depending on the cut-off) in France [37]. It is difficult to assess whether the reported data represent real differences in the seroprevalence of T. gondii infection or possibly reflect the use of different assays, different cut-offs for modified agglutination assays or perhaps intrinsic differences in the study samples regarding age and/or true origin of the animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…in [29, 30]). Recent studies in Europe have shown seropositivity rates of 1.7% in Greece [31], 10.8% in Spain [32], 3% [33] and 17.6% in Italy [34], 23% in the Czech Republic [35], 37.8% in Romania [36], and from 13 to 90% (depending on the cut-off) in France [37]. It is difficult to assess whether the reported data represent real differences in the seroprevalence of T. gondii infection or possibly reflect the use of different assays, different cut-offs for modified agglutination assays or perhaps intrinsic differences in the study samples regarding age and/or true origin of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…The risk was further emphasized by the isolation of a type III-like strain from horsemeat (originating from Canada) obtained from the first patient’s butcher [28]. Using MC-PCR, Aroussi et al [37] detected T. gondii DNA in 43% of 231 horsemeat samples from French supermarkets. Strain isolation was attempted from 118 samples by mouse bioassay, but no parasites were isolated, which the authors considered to reflect low distribution of cysts in skeletal muscles, therefore indicating a low risk of human T. gondii infection from consuming infected horsemeat [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such as IFAT requires special equipment or appropriate anti-species serum. MAT is simple, easy to perform and does not require those [7], however, some articles seems to call into question the fact that this technique can be applied to all animal species [28]. In this study, both IFAT and MAT were used and able to detect T. gondii antibodies in all inoculated chickens.…”
Section: Discussionmentioning
confidence: 90%